2015
DOI: 10.1186/s12890-015-0062-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes associated with Staphylococcus aureus and Pseudomonas aeruginosa airway infections in adult cystic fibrosis patients

Abstract: BackgroundStaphylococcus aureus (SA) is the most prevalent organism infecting the respiratory tract of CF children, and remains the second most prevalent organism in CF adults. During early childhood, SA infections are associated with pulmonary inflammation and decline in FEV1, but their clinical significance in adult CF patients is poorly characterized.MethodsWe conducted a retrospective cross-sectional study to determine the association between airway microbiology and clinical outcomes (FEV1, rate of pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 41 publications
7
55
0
Order By: Relevance
“…In their study, which also included more male patients (n = 55%), 24% of 84 patients were colonized by S . aureus [29]. In conjunction with our data this may suggest that male patients are more likely colonized by S .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In their study, which also included more male patients (n = 55%), 24% of 84 patients were colonized by S . aureus [29]. In conjunction with our data this may suggest that male patients are more likely colonized by S .…”
Section: Discussionsupporting
confidence: 84%
“…aureus or P . aeruginosa only, or neither of these pathogens [29]. In their study, which also included more male patients (n = 55%), 24% of 84 patients were colonized by S .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study examined S. aureus as a marker for CF lung disease in adult patients. In children with CF disease, the presence of S. aureus correlated with increased inflammation and decreased lung function (Ahlgren et al 2015). In contrast, S. aureus in adults could be a marker for milder disease, particularly if it coincides with reduced colonization by P. aeruginosa.…”
Section: Outcomes Of S Aureus-p Aeruginosa Interactionsmentioning
confidence: 99%
“…Studies of adults found S. aureus to be associated with a lower risk of mortality 30 , better lung function 31 , and a lower risk of exacerbations 32 . Therefore, S. aureus pathogenesis may either be context-dependent (that is, perhaps it is either more pathogenic either in children or in the absence of P. aeruginosa , or it adapts over time to become less pathogenic).…”
Section: Cf Microbiologymentioning
confidence: 99%